2022
DOI: 10.12998/wjcc.v10.i4.1296
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of acute cholecystitis in patients with confirmed COVID-19: Ten case reports and review of literature

Abstract: BACKGROUND Research concerning postoperative outcomes of confirmed coronavirus disease 2019 (COVID-19) patients revealed unfavorable postoperative results with increased morbidity, pulmonary complications and mortality. Case reports have suggested that COVID-19 is associated with more aggressive presentation of acute cholecystitis. The aim of the present study is to describe the perioperative assessment and postoperative outcomes of ten patients with confirmed severe acute respiratory syndrome cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Previous studies confirmed the biliary tropism of the novel coronavirus [ 1 ]. Literature reports suggested a more aggressive presentation of cholecystitis, regardless of the presence or not of cholelithiasis [ 1 ].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies confirmed the biliary tropism of the novel coronavirus [ 1 ]. Literature reports suggested a more aggressive presentation of cholecystitis, regardless of the presence or not of cholelithiasis [ 1 ].…”
Section: Introductionsupporting
confidence: 55%
“…Previous studies confirmed the biliary tropism of the novel coronavirus [ 1 ]. Literature reports suggested a more aggressive presentation of cholecystitis, regardless of the presence or not of cholelithiasis [ 1 ]. These associated biliary manifestations are considered to be the result of a dysregulated inflammatory response, rather than a direct viral injury [ 2 , 3 ].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, SARS-CoV-2 can directly affect the gallbladder’s epithelial cells because of the high expression of ACE2 receptors among them [ 99 ]. In a study by Bozada-Gutiérrez et al, a histopathological examination showed ischemia and necrosis (because of thrombosis in the small vessel), hemorrhagic changes, and acute inflammatory infiltrates in the gallbladder wall, accompanied by acute peritonitis [ 100 ].…”
Section: Aac Pathogenesis In Covid-19mentioning
confidence: 99%
“…During the COVID-19 pandemic, we observed an increased number of AC patients who presented with gangrenous acute cholecystitis. An early case series showed that COVID-19 infection and pneumonia were associated with GC with increased morbidity and mortality, mainly in elderly and frail patients [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%